Identifying and quantifying Mg-clays in well logs using new petrophysical methods: A case study from the Brazilian pre-salt. (February 2023) - Valle, Bruno; Dal' Bó, Patrick Führ; Nascimento dos Santos, Hélisson; Coelho, Pedro; Raitz, Gilberto; Arena, Michele; Santos, Jeferson; Favoreto, Julia; Ribeiro, Carolina; Borghi, Leonardo
Abstract: The Santos Basin, located in offshore southeast Brazil, is the site of several giant oilfields of the Pre-salt interval. The limestones from the Barra Velha Formation (Aptian in age) are complex, highly heterogeneous, and usually are associated with Mg-clays, being interpreted as deposited in an unusual alkaline lacustrine rift system that developed during the opening of the South Atlantic Ocean (Lower Cretaceous). The reservoirs of the Barra Velha Formation show exceptional reservoir quality and are sealed by marine evaporites of the Ariri Formation. Although clays traditionally present a negative impact on reservoir quality, Mg-clays (such as Mg-smectite, kerolite and talc) are prone to dissolution during diagenesis, which can increase the reservoir quality. However, in areas of the reservoir where Mg-clays are still present, they can significantly reduce it. The distribution of Mg-clays at the field, inter-field and basin scale has important implications for exploration and production. As these Mg-clays usually lack radioactive elements and therefore present a low gamma ray response, the usual petrophysical interpretation of clay-rich zones differs from the conventional method. This work proposes an algorithm to identify zones in a well with (1) presence of "pure Mg-clays" (i.e. not mixed with non-Mg-clays); (2) presence of "dirty Mg-clays" (i.e. mixed with non-Mg-clays or organic matter); and (3) absence of Mg-clays and another to quantify the Mg-clay volume in the wells. The study was carried out using well logs from 27 wells along with sidewall core samples. The occurrence of Mg-clays in the wells was confirmed by thin section description, supported by SEM- EDS and XRD analyses and allowed the understanding of the distribution of Mg-clays in the Sapinhoá Field, which are more abundant in structural lows due to better preservation whereas in higher structural positions clays were more affected by diagenetic alterations. The new algorithms proved to be reliable methods to perform both qualitative and quantitative detection of Mg-clay-rich zones using well logs and allowed the better identification of well-sections where this type of clay is present, providing a good-quality input for facies distribution. This study contributes to add new methodologies, which can be used in the improvement of petrophysical interpretations in zones with the presence of such complex clays and thus reducing the exploratory and development risks. Highlights: A new methodology is proposed to detect Mg-clay-rich zones in well logs. A new methodology is proposed to quantify Mg-clay content in well logs. Mg-clays were spread among most of the area, however dissolved/replaced in structural highs and preserved in structural lows. The Mg-clay distribution in the Sapinhoá Field is strongly controlled the by structural configuration.